1990
DOI: 10.1210/mend-4-5-669
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 5′-Flanking Sequence Deletions on Expression of the Human Insulin Gene in Transgenic Mice

Abstract: Expression of the human insulin gene was examined in transgenic mouse lines carrying the gene with various lengths of DNA sequences 5' to the transcription start site (+1). Expression of the transgene was demonstrated by 1) the presence of human C-peptide in urine, 2) the presence of specific transcripts in pancreas, but not in other tissues, 3) the specific immunofluorescence staining of pancreatic islets for human C-peptide, and 4) the synthesis and accumulation of human (pro)insulin in isolated islets. Dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 37 publications
2
40
1
Order By: Relevance
“…The inbred and Fl-hybrid mice were acclimatized 3 weeks before entering the immunization study at an age of 9 weeks. The transgenic mouse line (line 171) used for breeding in this study has previously been described [14][15][16][17]. Briefly, the transgenic mice are the progeny of the original founder mouse produced by microinj ecting an ll-kilobase human chromosomal DNA fragment including the insulin gene (1430 base pairs) into fertilized mouse eggs [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inbred and Fl-hybrid mice were acclimatized 3 weeks before entering the immunization study at an age of 9 weeks. The transgenic mouse line (line 171) used for breeding in this study has previously been described [14][15][16][17]. Briefly, the transgenic mice are the progeny of the original founder mouse produced by microinj ecting an ll-kilobase human chromosomal DNA fragment including the insulin gene (1430 base pairs) into fertilized mouse eggs [14].…”
Section: Methodsmentioning
confidence: 99%
“…The transgenic mice have tissue-specific expression in the pancreatic beta cells [16]. Expression of human insulin measured as percent of total insulin in the islets of Langerhans is approximately 50 % [17]. For this study the transgenic mice were backcrossed with normal BALB/c mice.…”
Section: Methodsmentioning
confidence: 99%
“…A B-like sequence adjacent to an enhancer core (GTGGAAAA; Weiher et al 19831 is conserved among the human, two mouse, and two rat insulin genes. The B-like and core elements are contained within the 48-bp insulin gene E 1 regulatory domain, which binds one or more islet-specific nuclear factors {Ohlsson and Edlund 1986; Philippe et al 1988) and is necessary for optimal expression in cultured insulinoma cells (Karlsson et al 1987) and in transgenic mice (Fromont-Racine et al 1990). The regulatory region of the glucagon gene contains a potential B element that overlaps the distal part of the 40-bp G1 region, which is critical for specific expression of the glucagon gene (Philippe et al 1988).…”
Section: Functional [3tf-1-binding Sites In Other Pancreatic Genesmentioning
confidence: 99%
“…There was also a perception that human insulin promoter constructs would not function in transfected rodent cells. However, these worries proved to be unfounded after it was later shown that there is a very high degree of sequence and functional conservation within the transcription factors that regulate the gene (e.g., 89% identity between rat and human PDX-1) and the human insulin promoter exhibited the expected pattern of activity in transgenic mice (9,10). As a result of the decision to concentrate on a detailed analysis of the rat insulin promoter, most of the literature on the insulin promoter pertains to this promoter.…”
mentioning
confidence: 99%